The role of migration and higher education policies in international academic mobility: the case of Indian researchers - Toma, S; Villares-Varela, M (International Migration Institute, 2015)
Governments are increasingly implementing policies aimed at attracting or retaining highly skilled migrants. While a growing number of studies examine the effectiveness of these efforts, the actual mechanisms through which policies may affect the aspirations and abilities to migrate of the highly skilled have not been questioned. This paper explores the roles of migration and higher education policies from both the origin and destination countries in the geographic mobility decisions of researchers, a highly skilled group that has been specifically targeted by such policies (e.g. scientific visas introduced by the EU). Focusing on Indian researchers and using in-depth qualitative interviews, we examine their decisions to study and/or work abroad, to stay or to return to India. More specifically, the paper asks (i) to what extent are (migration) policies driving Indian researchers’ decisions of whether and/or where to emigrate? and (ii) do policies attract or block Indian researchers from staying in their initial destination, re-migrating to another country or returning to India? In seeking to answer these questions, we consider not only the role of state migration policies, but also the institutional practices within higher education or research institutions.